Article VIII Acceptance by IMF Members : Recent Trends and Implications for the Fund. (Policy Papers; Policy Paper, 2006)
This paper reports on the work undertaken in this area since the 1992 review and seeks to encourage further progress in current account liberalization among the membership. Section II provides an overview of the legal framework; Section III studies recent trends in members' acceptance of Article VIII obligations, and analyzes the factors underlying these trends; Section IV outlines the possible economic (and financial) benefits of current account liberalization for Fund members; finally, Section V lays out the implications for surveillance, the enforcement of compliance with Article VIII obligations and technical assistance.